Has Kamala Harris abided by her parents’ advice? - Hasan, Md. Mahmudul (New Age, 2024)
Kamala Harris thought that caricaturing, denigrating, mocking and satirising Donald Trump alone would win her the election. She proved wrong and lost it to him. In a nutshell, by ignoring the plea for justice for the Palestinians, she insulted the intelligence of conscientious people in the US and around the world. She should have reassured the electorate that she would uphold human rights and justice both at home and internationally. That would have inspired a multitude of people to rally around her and could have won her the election. On a final note, I hope, after entering the White House as the 47th president of the United States, President Donald Trump will take emergency measures to rein in Israel’s genocidal behaviour and will not repeat Biden-Harris’s mistakes.